Pendampingan Tata Kelola Kelembagaan bagi Guru Taman Pendidikan al-Qur’an (TPQ) Tarbiyatul Mubtadi’in Desa Kencong Kecamatan Kepung Kabupaten Kediri - Ahmad Fauzi (LP3M IAIFA Kediri, 2020)
The Qur'an Education Park (TPQ) is an institution or community group that organizes a informal education of the Islamic religious type aimed at providing the teaching of reading Qur'an from an early age, as well as understand the fundamentals of Islam's Dinul in kindergarten, elementary school and or Madrasah Ibtidaiyah (SD/MI) or even higher. Furthermore, it is also known as kindergartens (TKQ), the educational and teaching institutions of the Qur'an for children aged 4 to 6 years. The purpose of TPQ is to provide basic provision for students (students) to be able to read the Qur'an properly and correctly in accordance with the science of TAJWID rules and also embed Islamic values for students (students) and equip students with religious sciences. From the results of mentoring to the TPQ Tarbiyatul Mubtadi'in found several problems and given recommendations as an effort to improve the quality of the institutions such as the following: 1). TPQ Tarbiyatul mubtadi'in immediately coordinate with the community leaders of the surrounding, with the hope of cooperation and the support of the death of Masayarakat. 2). Always strive to approach people around especially the students to consciously give the motivation of the Koran and learn religion to the children. 3). Always coordinate with the TPQ coordination Agency in Kediri Regency, thus gaining the latest knowledge in managing the TPQ Institute.